"I know my rights, but am I better off?": Institutions and disability in Uganda - Trudy Owens; Samantha Torrance (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2013)
Uganda is internationally recognised for its extensive legal and constitutional provisions for ensuring the rights of the disabled, in addition to the presence of a number of impairment-specific disabled persons' organisations (DPOs), which provide informal advocacy and support structures. Using a unique dataset from a sample of 579 physically disabled Ugandans collected by the authors in June 2012, we investigate the factors that are correlated with knowledge of the formal institutions of disability. Subsequently, we analyse whether this specific knowledge results in higher incomes for the respondents. There is evidence of a clear gender distinction both in terms of the knowledge of the formal institutions, and in income. Specifically, a woman's education, a measure of their social empowerment and membership of external networks being important correlates to knowledge, whilst for men; their age is the significant factor. In terms of earnings, we find that women are most likely to benefit from the knowledge of formal institutions of disability. Through our analysis we have sought to expand the literature on disability in developing countries using a unique approach that merges concepts from the social capital and institutions literature. Our results provide insights into how legislative tools may be used to ensure social and economic objectives are more mutually reinforcing, as well as the mechanisms through which information can be transmitted effectively amongst marginalised socioeconomic groups.
Keywords: O17; O22; 330; Development; Africa; Disability; Social Capital; Institutions